821 Comparative Effectiveness of Interventions to Reduce Ileus After Colorectal Surgery: A Network Meta-Analysis. (12th October 2021) - Ashcroft, J; Singh, A A; Ramachandran, B; Habeeb, A; Hudson, V; Meyer, J; Simillis, C; Davies, R J
Abstract: Aim: Several treatment strategies for post-operative ileus have been evaluated in randomised controlled trials. This network meta-analysis aimed to explore the relative effectiveness of these different therapies on their impact on ileus outcome measures. Method: A systematic review was conducted to identify randomised controlled trials reported up to 23rd April 2020. Indirect comparisons of all regimens were simultaneously compared using random-effects network meta-analysis. Results: A total of 48 randomised controlled trials, reporting any combination of five different outcome measures of time to flatus, stool, and solid diet tolerance, or nasogastric tube post-operative insertion, or length of stay following colorectal surgery were identified. In this network meta-analysis, early feeding was ranked first for time to solid diet tolerance (Mean Difference (hours) -58.845 CrI (-73.414, -43.150; rank 1 p = 0.960) and length of hospital stay (Mean Difference (hours) -2.326; CrI -3.510, -1.184; rank 1 p = 0.465) with high probability of first rank in the remainder of measures. Epidural analgesia was ranked first for time to flatus (Mean Difference (hours) -18.882; CrI -33.673, -3.435; rank 1 p = 0.286) and time to stool (Mean Difference (hours) -26.054; 95% CrI -66.417, 15.645; rank 1 p = 0.268). Conclusions: This network meta-analysis identified early feeding as the most efficacious therapeutic to reduce post-operative ileus in patients undergoing colorectal surgery. High quality studies of the efficacious therapeutics to reduce ileus following colorectal surgery highlighted in this review are required with established core outcome measures of gastrointestinal mobility.